The discovery of lymphatic system in the seventeenth century. Part I: the early history. Issue 4 (3rd July 2016) - Suy, Raphael; Thomis, Sarah; Fourneau, Inge
Abstract: The early history of lymphatic anatomy from Hippocrates (ca. 460–377 B.C.) to Eustachius (1510–1574). The presence of lymphatic vessels and lymph nodes was reported by ancient anatomists without any accurate knowledge of their true functions. Lymph nodes were described as spongy structures, spread over the whole body for the support of vulnerable body parts. Digestion was explained as being the resorption of clear chyle from digested food by the open endings of chyle vessels. The first insights into the place of lymphatic components within nutrition emanated from the medical school of Alexandria (fourth century B.C.) where vivisection was a common practice. Herophilus and Erasistratus described mesenteric veins full of clear liquid, air or milk. For Galen of Pergamum, (104–210) mesenteric lymph nodes also had a nutritional function. He described three different types of mesenteric vessels, namely, the arterial vessels, for the transport of spirituous blood to the intestines; the venous side branches of the portal vein, for the transport of nutritive blood from the liver to the intestines; and small vessels, from the intestines to the mesenteric lymph nodes (serous lymph vessels?). According to Galen, chyle was transported via the above-mentioned mesenteric venous vessels from the intestines to the portal vein and liver, where it was transformed into nutritive blood. This doctrine would be obliterated in the seventeenth century by the discovery of systemic circulation and of the drainage of chyle through a thoracic duct to the subclavian veins.